Assessment of accelerometer-derived data in the context of seat height changes in cycling and the impact on running in triathlon - Evans, S. A.; James, D. A.; Rowlands, D.; Lee, J. B. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
Triathlon has been an Olympic sport since the 2000 Sydney Olympics and has developed rapidly, leading to variations in race categories. Although running after cycling necessitates a postural change from a non-weight-bearing activity to a weight bearing one, no study has quantified the magnitude of trunk acceleration during cycling in different seat positions and the consequential effect on running. Therefore, this study was conducted to evaluate the effectiveness of a triaxial accelerometer to determine acceleration magnitudes of the trunk in a 20 km outdoor cycling event in two seat positions that were immediately followed by a 5 km overground run. Interpretation of data was evaluated based on cadence changes while triathletes cycled in an aerodynamic position in two seat positions. Running data was evaluated based on sinusoidal curves and foot strike peaks. The evaluation of accelerometer derived data within a characteristic overground setting suggests that cycling in an adjusted seat position significantly reduced trunk acceleration in both longitudinal and mediolateral directions with large effects (p < 0.0001, d > 0.9). A significant and large effect was found in both longitudinal and anteroposterior trunk acceleration in post-cycle running between seat positions (d > 0.9, p < 0.0001). In the longitudinal direction, a significant reduction in trunk acceleration occurred when running after the seat was adjusted with participants completing the 5 km run faster (21:55 ± 3:17 min compared to 22:05 ± 2:53 min). The results suggest that when the seat position is adjusted based on individual anthropometrics, overall trunk acceleration magnitude is reduced in both cycling and running. Accessible and practical sensor technology could be beneficial for postural considerations in triathlons.